Perception of Emotions from Static Postures - Shaarani, Ahmad Shaarizan (Springer, 2008)
Human synthetic characters in any computer simulated environment need to be capable of behaving the appropriate way of expressing emotion like normal human do. If the characters fail to express the suitable emotional expression, they will likely to break the users mood and belief. These imply that the key problem in designing synthetic characters is to make them believable in their overall behavior. Therefore the study was directed to construct human synthetic characters that can improve humans respond as well as identify intensity rating of emotions. Ekmans six emotional expressions [1], which are happiness, sadness, anger, surprise, fear and disgust were used because these basic emotions are clear, widely accepted and sufficient. An experiment was conducted to measure believable emotional expression from static images. Sets of virtual human static images of posed expressions of emotions were shown to the subjects. A total of 36 thirty-six volunteers (18 men and 18 women) took part in the experiment. The mean age was 29 years old. The subjects were asked to recognize the expressions by grouping them into six basic emotions and provide the level of emotion for each posture to study the intensity-rating tasks.